Introduction to types of scientific writing research for science teachers at SMPS Gita Surya Eban - Astriani Dewi, Ni Putu Yuni; Rita Sila, Vinsensia Ulia; Sele, Yunawati; Shidik, Muhammad Amran; Simarmata, Justin Eduardo (Talenta Publisher, 2020)
The purpose of this community service activity is to provide an introduction to training in making scientific papers for teachers of Gita Surya Eban Junior High School. Furthermore, the background for the implementation of this socialization is to provide information about how to make educational and non-educational scientific papers, as well as provide information to teachers on the importance of making scientific papers as a prerequisite for promotion and class. This service activity has been carried out since November 2020 with 18 participants. This activity is carried out by introducing the types of research that are experimental in the laboratory.